2017
DOI: 10.3847/1538-4357/aa7cf4
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Collapse of the Presolar Dense Cloud Core and Injecting Short-lived Radioisotopes with a Shock Wave. V. Nonisothermal Collapse Regime

Abstract: Recent meteoritical analyses support an initial abundance of the short-lived radioisotope 60 Fe that may be high enough to require nucleosynthesis in a core collapse supernova, followed by rapid incorporation into primitive meteoritical components, rather than a scenario where such isotopes were inherited from a well-mixed region of a giant molecular cloud polluted by a variety of supernovae remnants and massive star winds. This paper continues to explore the former scenario, by calculating three dimensional,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 54 publications
6
50
0
Order By: Relevance
“…This cooling, however, is only appropriate in optically thin regions, and hence is invalid in high density regions. Boss (2017) extended the models to later, higher density phases of evolution by employing a barotropic equation of state once densities high enough to produce an optically thick protostar arose, i.e., for densities above some critical density ρ cr (Boss 1980). The same approach is employed here, in addition to the sink particle artifice, to handle high density regions.…”
Section: Numerical Hydrodynamics Codementioning
confidence: 99%
See 2 more Smart Citations
“…This cooling, however, is only appropriate in optically thin regions, and hence is invalid in high density regions. Boss (2017) extended the models to later, higher density phases of evolution by employing a barotropic equation of state once densities high enough to produce an optically thick protostar arose, i.e., for densities above some critical density ρ cr (Boss 1980). The same approach is employed here, in addition to the sink particle artifice, to handle high density regions.…”
Section: Numerical Hydrodynamics Codementioning
confidence: 99%
“…In higher density regions, the gas pressure p is defined to depend on the gas density as p ∝ ρ γ , where the barotropic exponent γ equals 7/5 for molecular hydrogen gas. Boss (2017) tested several different choices for ρ cr in order to find a value that reproduced approximately the thermal evolution found in the spherically symmetrical collapse models of Vaytet et al (2013), who studied the collapse of solar-mass gas spheres with a multigroup radiative hydrodynamics code. Boss (2017) found that ρ cr ∼ 5 × 10 −13 g cm −3 was the best choice for reproducing the Vaytet et al (2013) thermal evolutions.…”
Section: Numerical Hydrodynamics Codementioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of astrophysical scenarios have been proposed for the origin of the solar system (see e.g., Boss 1995;Cameron et al 1995;Wasserburg et al 2006;Sahijpal & Soni 2006;Gaidos et al 2009;Gounelle et al 2009;Huss et al 2009;Sahijpal and Gupta 2009;Dauphas and Chaussidon 2011;Boss 2017;Liu 2017;Lugaro, Ott & Kereszturi 2018;Jones et al 2019). Evolved stars ranging from massive Wolf-Rayet (WR) stars, Supernovae (SN Ia, Ib/c, SN II) and Asymptotic Giant Branch (AGB) stars have been proposed along with distinct stellar environments associated with the birth of the solar system.…”
Section: Introductionmentioning
confidence: 99%
“…Various stellar nucleosynthetic processes can contribute towards the predicted abundance of the SLRs (Cameron et al 1995;Wasserburg et al 2006;Sahijpal & Soni 2006;Gaidos et al 2009;Gounelle et al 2009;Huss et al 2009;Sahijpal and Gupta 2009;Dauphas and Chaussidon 2011;Boss 2017;Dwarkadas et al 2017;Liu 2017;Lugaro et al 2018;Jones et al 2019).…”
Section: Introductionmentioning
confidence: 99%